Visual evoked potentials in cochlear implanted children - Runjić, Nađa; Vranić, Đurđica; Mildner, Vesna (2007)
Cochlear implant is the most sophisticated hearing aid that provides the base for hearing and speech development. The system for space perception, spacioception, essential for the grammar of hearing and speech development, is consisted of hearing function, visual one, vestibuloception, touch and proprioception. The system for testing the evoked potentials with simultaneous cartographical presentation of cortical activation provides good insight in correspondence of spacioceptive functions. The aim of this study was to investigate the changes in visual evoked potentials and cartographical characteristics in cochlear implanted children. Ten children, cochlear implant users, aged 5-8 years were tested. Control group consisted of 10 children with normal hearing and speech development, and 10 hearing impaired children with standard hearing aids. Complete diagnostic evaluation were performed included ophtalmological, otoneurological, logopedic and psychological evaluation. Subjects and controls were examined by checkerboard pattern reversal visual evoked potentials (VEP) according to the 2004. European standards. Cortical cartography was simultaneously performed by Neuroscan 32-electrode system using Scan 4.3 software for data analysis. The results show that cochlear implanted children have more efficient processing of visual information on prechiasmal level in comparison to well hearing children and standard hearing aid users. The characteristics of talamocortical processing are correlated to the development level of psycholinguistcs abilities.
Poster - Knjiga sažetaka: The second Croatian Congress of Neuroscience, May 18 and 19, 2007. Zagreb
Projekt MZOS
Projekt MZOS
ENG